The Relative Reinforcing Value of Cookies Is Higher Among Head Start Preschoolers With Obesity - Eagleton, Sally G.; Temple, Jennifer L.; Keller, Kathleen L.; Marini, Michele E.; Savage, Jennifer S. (Frontiers in Psychology, 2021)
The relative reinforcing value (RRV) of food measures how hard someone will work for a high-energy-dense (HED) food when an alternative reward is concurrently available. Higher RRV for HED food has been linked to obesity, yet this association has not been examined in low-income preschool-age children. Further, the development of individual differences in the RRV of food in early childhood is poorly understood. This cross-sectional study tested the hypothesis that the RRV of HED (cookies) to low-energy-dense (LED; fruit) food would be greater in children with obesity compared to children without obesity in a sample of 130 low-income 3- to 5-year-olds enrolled in Head Start classrooms in Central Pennsylvania. In addition, we examined individual differences in the RRV of food by child characteristics (i.e., age, sex, and reward sensitivity) and food security status. The RRV of food was measured on concurrent progressive-ratio schedules of reinforcement. RRV outcomes included the last schedule reached (breakpoint) for cookies (cookie Pmax) and fruit (fruit Pmax), the breakpoint for cookies in proportion to the total breakpoint for cookies and fruit combined (RRV cookie), and response rates (responses per minute). Parents completed the 18-item food security module to assess household food security status and the Behavioral Activation System scale to assess reward sensitivity. Pearson’s correlations and mixed models assessed associations between continuous and discrete child characteristics with RRV outcomes, respectively. Two-way mixed effects interaction models examined age and sex as moderators of the association between RRV and Body Mass Index z-scores (BMIZ). Statistical significance was defined as p < 0.05. Children with obesity (17%) had a greater cookie Pmax [F (1, 121) = 4.95, p = 0.03], higher RRV cookie [F (1, 121) = 4.28, p = 0.04], and responded at a faster rate for cookies [F (1, 121) = 17.27, p < 0.001] compared to children without obesity. Children with higher cookie response rates had higher BMIZ (r = 0.26, p < 0.01); and RRV cookie was positively associated with BMIZ for older children (5-year-olds: t = 2.40, p = 0.02) and boys (t = 2.55, p = 0.01), but not younger children or girls. The RRV of food did not differ by household food security status. Low-income children with obesity showed greater motivation to work for cookies than fruit compared to their peers without obesity. The RRV of HED food may be an important contributor to increased weight status in boys and future research is needed to better understand developmental trajectories of the RRV of food across childhood.